1969
DOI: 10.2136/sssaj1969.03615995003300040033x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Peats as Related to Degree of Decomposition

Abstract: Important physical characteristics, such as water retention, water yield coefficient, and hydraulic conductivity, vary greatly for representative northern Minnesota peat materials. The differences are related to the degree of decomposition, which largely determines the porosity and pore size distribution. Fiber content (> 0.1 mm) and bulk density are properties often measured to indicate the degree of decomposition of peat materials and are criteria used to distinguish fibric, hemic, and sapric peat types.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
201
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(217 citation statements)
references
References 0 publications
14
201
0
2
Order By: Relevance
“…In most sites layers of both mineral and organic soils were found. The data published by Boelter (1969) and Brandyk et al (1996) for peat soils indicated that moisture retention characteristics were dependent on the degree of decomposition. In all cases, organic soils contained more water (Table 3), and a higher degree of humification results in finer particles and, consequently, organic soils had more water at any given tension (Kellner and Halldin 2002).…”
Section: Discussionmentioning
confidence: 91%
“…In most sites layers of both mineral and organic soils were found. The data published by Boelter (1969) and Brandyk et al (1996) for peat soils indicated that moisture retention characteristics were dependent on the degree of decomposition. In all cases, organic soils contained more water (Table 3), and a higher degree of humification results in finer particles and, consequently, organic soils had more water at any given tension (Kellner and Halldin 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Given the difficulties (choice of extractant, neoformed products) encountered by the researchers working on European peat bogs [7][8][9] and after a number of laboratory tests, we decided to use the following protocols and to compare the results obtained with 2 g of test sample per 100 mL of solution (n × 5): extraction with sodium pyrophosphate at pH 10 for 16 h with stirring, extraction with 0.1 N sodium hydroxide (pH 12) for 16 h with stirring.…”
Section: Extraction Of Humic Compoundsmentioning
confidence: 99%
“…Boelter (1969) provided regression equations for calculating water content from fiber content of organic soils. Equations were provided for 0.1 bar and 15 bar suctions (permanent wilting point).…”
Section: Estimation Of Available Water Capacitymentioning
confidence: 99%